Homozygous mutation in DNALI1 leads to asthenoteratozoospermia by affecting the inner dynein arms - Sha, Yanwei; Liu, Wensheng; Nie, Hua; Han, Lu; Ma, Chunjie; Zhang, Xiaoya; Xiao, Ziyi; Qin, Weibing; Jiang, Xiaoming; Wei, Xiaoli (Frontiers in Endocrinology, 2023)
Asthenozoospermia is the most common cause of male infertility. Dynein protein arms play a crucial role in the motility of sperm flagella and defects in these proteins generally impair the axoneme structure and affect sperm flagella function. In this study, we performed whole exome sequencing for a cohort of 126 infertile patients with asthenozoospermia and identified homozygous DNALI1 mutation in one patient from a consanguineous family. This identified homozygous mutation was verified by Sanger sequencing. In silico analysis showed that this homozygous mutation is very rare, highly pathogenic, and very conserved. Sperm routine analysis confirmed that the motility of the spermatozoa from the patient significantly decreased. Further sperm morphology analysis showed that the spermatozoa from the patient exhibited multiple flagella morphological defects and a specific loss in the inner dynein arms. Fortunately, the patient was able to have his child via intracytoplasmic sperm injection treatment. Our study is the first to demonstrate that homozygous DNALI1 mutation may impair the integration of axoneme structure, affect sperm motility and cause asthenoteratozoospermia in human beings.